Glocalizing Metamorphosis: A Post-Humanist Critique of Hybrid Romance in The Legend of White Snake and The Little Mermaid (Asian Journal of Social Science Studies, 2022)
As a transcultural archetype in both Eastern and Western mythology, metamorphosis is the main clue in The Little Mermaid by Danish writer Hans Christian Andersen and The Legend of the White Snake rewritten by Feng Menglong, which both demonstrate a cross-species romance between human beings and half-human-half-animal entities. Thus, by paralleling the story of metamorphosis in Eastern and Western cultural contexts, this paper attempts to investigate the ―sharedness‖ rather than ―sameness‖ between the metamorphosis tradition by creating a glocal heterotopia, revealing a possible post-humanistic potential for disrupting the differential human-animal categorization, while the tragic ending of both romances also indicates a shared pessimistic view on the establishment of nature-culture continuum and the underlying anthropocentric conception in the 17th century China and 19th century Europe.